A kinetic analysis and recommendations for elite swimmers performing the sprint start - Mason, B.; Alcock, A.; Fowlie, J. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The object of this project was to identify on block characteristics of superior grab starts and identify if these also applied to the track start. Six elite swimmers were selected for the study. The characteristic most closely observed in excellent off block starting ability for the grab start was peak power normalised to body mass. Average power and maximum horizontal propulsive force normalised to body mass were closely linked as was work output, but not as highly as the previous parameters. Horizontal velocity off the block was not a good predictor of off block ability as the angle at which the swimmer left the block played an important role in the outcome. Time off the block and first movement time were poor indicators of starting ability. Similar characteristics, but with completely different force and power profiles, were evident for swimmers that utilised a track start.